2020
DOI: 10.1002/lary.28750
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Analysis of the Vocal Folds Using Computed Tomography: Effects of Age, Height, and Gender

Abstract: Objective The goal of this study was to use computed tomography (CT) volumetric analysis to assess the effect of age, gender, height, body mass index (BMI), and ethnicity on vocal fold volume in patients with normal larynges. Study Design Retrospective cross‐sectional study. Methods Vocal fold length, width, and height were measured in a total of 105 patients without a history of laryngeal or thyroid pathology on thin‐section soft‐tissue neck CTs. The product of the three dimensions was used to calculate vocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This smaller cross-sectional area has been shown in computed tomography studies to have a difference in the size of glottal folds. Nevertheless, computed tomography studies have shown gender differences in the size of glottal folds [ 23 ], reporting that glottal folds movement was correlated with fundamental frequency in healthy subjects [ 24 ]. These results propose that the height of the voice and aerosol production in the glottis are involved in the dynamics of small aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…This smaller cross-sectional area has been shown in computed tomography studies to have a difference in the size of glottal folds. Nevertheless, computed tomography studies have shown gender differences in the size of glottal folds [ 23 ], reporting that glottal folds movement was correlated with fundamental frequency in healthy subjects [ 24 ]. These results propose that the height of the voice and aerosol production in the glottis are involved in the dynamics of small aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between vocal fold atrophy and age has been probed in many studies, 3,15,16 including a recent study that performed volumetric analysis of vocal folds using computed tomography (CT), which found that age was not linearly associated with vocal fold volume. 15 Vocal fold histologic and physiologic changes that are associated with ageing include calcification of the hyaline cartilages, decreased mucosal mucoserous function, decreased neuromuscular control, mucosal atrophy and changes in the composition of the vocal folds themselves. 2,3,17,18 However, these findings are not necessarily assessed during laryngoscopy and there remains a lack of correlation between patient age and video-laryngoscopy examination findings.…”
Section: Findings In the Context Of Other Studiesmentioning
confidence: 99%
“…Measured and predicted parameter values and the associated stress-strain curves are discussed in Section 5. The conclusion is formulated in Section 6. iv Table 1: Overall properties for M5, MRI and EPI replicas and values reported for a male adult [13,14,4,15] and using soft tissue density 1.03 g/cm 3 [3,16]: right-left length L x , posterior-anterior length L y , inferior-superior length L z , volume V V F and mass m V F . Mu) of a human VF depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1(a) are summarised in Table 1 indicating right-left length L x , posterior-anterior length L y , inferior-superior length L z , total mass m V F and volume V V F . As a reference, typical values reported for the VF of a male adult are given as well [13,14,4,15,3,16].…”
Section: Introductionmentioning
confidence: 99%